Pengaruh Usia Dalam Memoderasi Pengaruh Tingkat Kesiapan Teknologi Pada Niat Konsumen Dalam Menggunakan Layanan SMS Banking Di Kota Denpasar - Pramana, Duta Wahyu; Mandala, Kastawan (E-Jurnal Manajemen, 2014)
SMS banking is one of the features of mobile banking services . Intention to use SMS Banking service is strongly influenced by the level of technological readiness and the role of age had a major impact on the level of technological readiness of the customers so that they can decide to use or not the SMS Banking service . The purpose of this study was to determine the role of age in moderating the influence of technology readiness level of the consumer 's intention to use SMS Banking service in Denpasar. Data collection techniques used in this study is through the distribution of questionnaires to customers who know the SMS Banking service but have not used it . The questionnaire measured with a Likert scale with 22 indicators . The sample size used in the study was 110 respondents were taken by purposive sampling technique . The analytical method used is multiple linear regression analysis . The results of the study showed that age proved to be able to moderate the influence of the four dimensions of technology readiness level ( optimism , innovativeness , discomfort , and insecurity ) on the intention to use SMS Banking service . Future studies are expected to be able to add another variable to the variation in respondents' answers .
Keywords: Demographic, Technology Readiness Index, Intention To Use